An archaeal nucleoid-associated protein binds an essential motif in DNA replication origins - Rajkumar Dhanaraju; Rachel Y. Samson; Xu Feng; Alessandro Costa; Giovanni Gonzalez-Gutierrez; Stephen D. Bell (Nature Communications)
Abstract DNA replication typically has defined start sites, or replication origins, which are designated by their recognition by specific initiator proteins. In addition to initiators, general chromatin or nucleoid-associated proteins have been shown to play roles in modulating origin efficiency in eukaryotes and bacteria. The role of chromatin proteins in origin function in the archaeal domain of life is poorly understood. Here, we describe a dissection of sequences elements required for in vivo function of an archaeal DNA replication origin. Our data reveal a hitherto uncharacterized sequence element, the ucm, is required for origin activity. We identify a protein, UBP, that interacts with the ucm and additionally with hundreds of other sites on the genome. We solve the crystal structure of UBP alone and in complex with ucm DNA, and further show that UBP interacts with the MCM replicative helicase. Taken together, our data provide evidence that UBP functions as a general nucleoid-associated protein that plays a key role in facilitating the egress of the MCM replicative helicase from DNA replication origins.